Association between mitochondrial DNA and cognitive impairment in schizophrenia: study protocol for a Mexican population - García-de la Cruz DD (Dove Medical Press, 2019)
Dulce Dajheanne García-de la Cruz,1,2 Isela Esther Juárez-Rojop,1 Carlos Alfonso Tovilla-Zárate,3 José Jaime Martínez-Magaña,1,4 Alma Delia Genis-Mendoza,4,5 Humberto Nicolini,4 Thelma Beatriz González-Castro,1,6 Crystell Guadalupe Guzmán-Priego,1 Nancy Adanelly López-Martínez,1,2 Javier Antonio Hernández-Cisneros,1 Francisco Caballero-Prado71División Académica de Ciencias de la Salud, Universidad Juárez Autónoma de Tabasco, Villahermosa, Tabasco, Mexico; 2Investigación y Enseñanza, Hospital Regional de Alta Especialidad de Salud Mental, Villahermosa, Tabasco, Mexico; 3División Académica Multidisciplinaria de Comalcalco, Universidad Juárez Autónoma de Tabasco, Villahermosa, Tabasco, Mexico; 4Laboratorio de Enfermedades Psiquiátricas y Neurodegenerativas, Instituto Nacional de Medicina Genómica, Mexico City, Mexico; 5Hospital Psiquiátrico Infantil “Dr. Juan N. Navarro”, Mexico City, Mexico; 6División Académica Multidisciplinaria de Jalpa de Méndez, Universidad Juárez Autónoma de Tabasco, Jalpa de Méndez, Tabasco, Mexico; 7Servicio de Salud Mental, Hospital Regional de Alta Especialidad “Dr. Juan Graham Casasús”, Villahermosa, Tabasco, MexicoBackground: Circulating cell-free mitochondrial DNA (cf-mtDNA) fragments in blood plasma have been reported in patients with schizophrenia (SZ). Although the relationship of cf-mtDNA to the cognitive status of patients with SZ has not yet been explored, it is known that cognitive impairment in SZ compromises the functional and social capacity of these patients and diminishes their quality of life. In this sense, the assessment of the severity of cognitive impairment in a Mexican population with SZ and its association with cf-mtDNA levels in blood plasma may provide the possibility of using cf-mtDNA as a biomarker to determine the status of the disease and the possible ensuing changes over time. Methods: Subjects for a case–control study will be recruited. cf-mtDNA obtained from blood plasma will be quantified by real-time polymerase chain reaction, using melting curve technology with SYBR green as amplification marker. Patients with SZ will be grouped into those with severe, mild, and no cognitive impairment according to Montreal Cognitive Assessment scale scores, to determine differences between cognitive performance and cf-mtDNA levels in blood plasma. Ethics and communication: This study has been approved by the ethics and investigation committees of the High Specialty Regional Hospital of Mental Health (Hospital Regional de Alta Especialidad de Salud Mental); project No. HRAESM/DG/RP/1128/2018. We plan to communicate our research findings in scientific conferences and in peer-reviewed journals. Conclusion: It is known that cognitive dysfunction provokes negative effects in an SZ patient´s life. This project aims to provide better knowledge about the role of cf-mtDNA in the pathogenesis of cognitive impairment in SZ, as an attempt to achieve improvements to the existing treatments, thereby helping to prevent major cognitive deterioration.Keywords: schizophrenia, cognitive impairment, mitochondrial dysfunction, mitochondrial DNA, neurodegeneration